Exploring the relationship between doctoral students' experiences and research community positioning. Issue 1 (2nd January 2017) - Sala-Bubaré, Anna; Castelló, Montserrat
ABSTRACT: Despite the growing number of studies exploring PhD students' experiences and their social relationships with other researchers, there is a lack of research on the interaction between the type of experiences and the social agents involved, especially in relation to not only problems and challenges, but also to positive emotions and experiences. In this study, we addressed this gap exploring the relationship between four ecology doctoral students' most significant experiences and their perceived position in the research community. Additionally, we aimed at exploring the utility of a methodological device with two instruments, Journey Plot and Community Plot . Results showed, in one hand, that both positive and negative experiences were significant in students' trajectories, but the proportion varied greatly across participants. Supervisors were related to negative experiences, whereas the broader community was mostly source of positive experiences. Research writing and communication experiences were significant in relation to all the social agents, while other contents of experience were restricted to the smallest social layers (e.g. research motives were confined to the individual layer, and research organization to the individual and supervisor layers). Relationships between the type of experiences and participants' position in the community were found and implications for doctoral education discussed.